UJI TARIK (STRESS MPA) GUNA MENENTUKAN ALTERNATIF PEMILIHAN MATERIAL BAJA DENGAN PENDEKATAN ANOVA 1 ARAH - Abdullah, Ishlahuddin; Rohmat, Rohmat (JUSTI (Jurnal Sistem dan Teknik Industri), 2024)
Practicum is an academic process taken in an educational institution. The use of materials in practicum is very important. By choosing materials for appropriate practical activities, it will produce good practicum output. In this study, alternative steel was selected in order to obtain steel that meets the needs of the practicum. The results of the tensile test of 3 steel materials with the one-way anova method obtained a value of 0.187 > 0.05, which means that the P-Value is greater and it can be concluded that there is no significant difference between steel material A, steel B and Steel Bja C. This means that the practicum process activities can choose the type of steel material at the most affordable price because at a price that is within reach, you have obtained a type of steel material that has the same quality as steel Other.